Phagophores evolve from recycling endosomes. Issue 8 (3rd August 2018) - Puri, Claudia; Vicinanza, Mariella; Rubinsztein, David C.
ABSTRACT: The membrane origins of autophagosomes have been a key unresolved question in the field. The earliest morphologically recognizable structure in the macroautophagy/autophagy itinerary is the double-membraned cup-shaped phagophore. Newly formed phosphatidylinositol 3-phosphate (PtdIns3P) on the membranes destined to become phagophores recruits WIPI2, which, in turn, binds ATG16L1 to define the sites of autophagosome formation. Here we review our recent study showing that membrane recruitment of WIPI2 requires coincident detection of PtdIns3P and RAB11A, a protein that marks recycling endosomes. We found that multiple core autophagy proteins are more tightly associated with the recycling endosome compartment than with endoplasmic reticulum (ER)-mitochondrial contact sites. Furthermore, biochemical isolation of the recycling endosomes confirmed that they recruit autophagy proteins. Finally, fixed and live-cell imaging data revealed that recycling endosomes engulf autophagic substrates. Indeed, the sequestration of mitochondria after mitophagy stimulation depends on early autophagy regulators. These data suggest that autophagosomes evolve from the RAB11A compartment.